The Problems of Using the Zoom Cloud Meeting Application as an Online Learning Facility for Class X German at SMA Laboratorium UM - Gloria Vincentia Riyadi; Dewi Kartika Ardiyani (Universitas Negeri Malang, 2022)
The purpose of this study was to describe student responses in learning activities, the problems that students facing, and the factors causing the problem to the online learning process using the Zoom Cloud Meeting application. The data sources for this study were 29 German high school seniors at SMA LABORATORIUM UM who were at the language level equivalent to A1 GER. Data obtained are from observation, closed questionnaires, and interviews, with the type of qualitative descriptive research. The results of the study indicate that several problems have the potential to hinder the online learning process of senior high school students in German language classes, such as technical obstacles to using, technical internet connections, and the other problems that limit the access of students to the full-featured zoom application that hinders the learning process from running optimally.